RESPONSE OF COCONUT TO INCREASING LEVELS OF LEAF PRUNING AND ITS IMPLICATIONS ON FARM PRODUCTIVITY - S.S. Magat; L.H. Canja; R.Z. Margate (International Coconut Community, 1994)
Effects on nut production and copra (wt/nut and yield/tree of four leaf pruning conditions (LP): control (no LP); LP from leaf 24; leaf 19 and leaf 14 with 31, 23, 18 and 13, remaining leaves on each palm, respectively, was studied on adult bearing palms at the Davao Research Center, Philippine Coconut Authority. As a reference point, leaf 1 is considered as the youngest expanded leaf, while leaf 19, the one supporting the 7‑8 month old developing nuts or buko. Except in the first year of LP of which nut and copra yields under all LP conditions were similar to the unpruned palms, the following second and third years of LP indicated that leaf pruning from leaf 19 or maintaining only the 18 younger, upper leaves of the tree crown strongly showed the capability of the coconut to still support the normal development and maturity of nuts. As a result of LP, sunlight transmission to intercrops increased by about 120% compared to unpruned palms. This was translated to higher intercrop yield of corn (2.16 t increased to 3.71 t/ha) which is strongly attributed to the average 4,000 ft candles of sunlight (190.5 PAR) observed with LP from leaf 19 and the rest of the leaves below. In relation to increased sunlight transmission, intercropping, water economy and drought tolerance, pest and disease control and added income from pruned leaves, implications of LP are pointed out.